Barriers and opportunities in the development of rural industries: a case study of silverware and batik production in Kelantan, Peninsular Malaysia - Redzuan, Ma'rof; Aref, Fariborz (IDOSI Publications, 2009)
The main objective of this study is to identify the barriers and opportunities faced by handicraft enterprises in underdeveloped regions of Malaysia. The study is based upon both quantitative and qualitative analysis. The findings showed that the handicraft industries are very closely affiliated to the community and they provide significant employment opportunities to the local people; the industries are presently encountering several constraints in relation to the quality and availability of both physical and human resources. Findings also showed age appears to represent an important factor in both constraining the industries' development and in offering a ray of optimism for future development and the majority of the entrepreneurs preferred that the development of their industries should involve evolutionary or gradual change rather than a rapid transformational development. In relation to the rural non-farm sector, the findings of the study have shown handicraft industries play an important role in the rural society by providing occupation and income.